The Gly482Ser polymorphism of the peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) is associated with type 2 diabetes in Tunisian population. Issue 4 (October 2015) - Jemaa, Zeineb; Kallel, Amani; Sleimi, Chaker; Mahjoubi, Imen; Feki, Moncef; Ftouhi, Bochra; Slimane, Hedia; Jemaa, Riadh; Kaabachi, Naziha
Abstract: Background and aims: Peroxisome proliferator-activated receptor-γ co-activator-1α (PGC-1α) is a transcriptional co-activator involved in adaptive thermogenesis, skeletal muscle metabolism, fatty acid oxidation, and gluconeogenesis. Several studies have suggested that the common PGC-1α polymorphism Gly482Ser (rs8192678) may be associated with risk of type 2 diabetes (T2D), with conflicting results. The aim of this study was to analyze whether the Gly482Ser variant is a risk factor for development of T2D in Tunisian population. Methods: In a case–control study 487 unrelated patients with type 2 diabetes and 402 apparently healthy controls were recruited from January 2008 to August 2010. The Gly482Ser polymorphism was determined by PCR-RFLP analysis. Results: A significant difference in genotypes distribution was observed between patients (Gly/Gly: 34.1%; Gly/Ser: 47.1%; Ser/Ser: 18.5%) and controls (Gly/Gly: 43.8%; Gly/Ser: 42.3%; Ser/Ser: 13.9%) ( χ 2  = 9.44, p  = 0.009). The T2D patient group showed a significant higher frequency of the Ser allele compared to the controls (43% vs. 34%; OR: 1.35, 95% [CI]: 1.11–1.65, p  = 0.002). The association between the Gly482Ser polymorphism and T2D remained significant after adjustment for other well-established cardiovascular risk factors. Conclusions: In the current study, a significant and independent association between the Gly482Ser polymorphism (rs8192678) of the PGC-1α gene and T2D in the Tunisian population was found.